M MANAJEMEN PENERIMAAN PESERTA DIDIK BARU SECARA ONLINE BERBASIS PRESTASI, REGULER, DAN AFIRMASI DI MAN 1 ACEH TIMUR - Nurfitah Zahara; Nurasiah Nurasiah (Program Studi Manajemen Pendidikan, 2026)
This study aims to analyze the management of the online new student admission process (PPDB) based on the merit, regular, and affirmative action tracks at MAN 1 East Aceh. The study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research informants consisted of the madrasah principal, the PPDB committee, and system operators, all of whom were selected through purposive sampling. The results show that online PPDB management is carried out through four stages: planning, organizing, implementation, and supervision and monitoring. The PPDB process utilizes Google Forms in two registration waves, with selection based on the completeness of documents and report card grades according to the respective admission tracks. The use of Google Forms simplifies the registration process and data management; however, it still has limitations because it does not yet support integrated document verification, registration pathway sorting, and data security. Overall, online PPDB management at MAN 1 Aceh Timur has been effective, transparent, and capable of supporting a fair and equitable student admission process.